A Study of Science Learning Unit Development of the Teacher under Nakhon Ratchasima Provincial Administrative Organization - Panitanung, Sirikanya; Tanok, Somkiat (Ratchaphruek Journal, 2014)
The purposes of this study were: 1) to study the learning unit development in the learning area of science for teachers under Nakhon Ratchasima Provincial Administrative Organization on the preparation for the learning unit management and; 2) to compare the learning unit development in the learning area of science for teachers in concord with the 2008 school curriculum, classified by field of study and teaching experience. The sample group consisted of 181 teachers teaching in the learning area of science from 58 schools in the academic year of 2010; 3 teachers derived from simple random sampling were selected from each school, except 5 teachers from Buayai school, 5 teachers from Prathai school, and 6 teachers from Tiam Udom Sueksa Nomklao school due to the large size of schools. The instrument used to collect data was a questionnaire of 102 items. Data were statistically analyzed by applying percentage, mean, standard deviation, and t-test (independent samples t-test). The results of the study indicated that the preparation for the learning unit development in the learning area of science for teachers under Nakhon Ratchasima Provincial Administrative Organization on the learning unit management, the subject-scope management, the goal setting, the learning proof determination, the teaching and learning plan, the application, and the evaluation of the learning unit in general. Each aspect was at the high level; the problem of the learning unit management, the subject-scope management, the goal setting, the learning proof determination, the teaching and learning plan, the application, and the evaluation of the learning unit in general. Each aspect was at the low level; and the comparison of the management and the problem of the learning unit development by using field of study and teaching experience in general was not different at the statistically significant level of .05. (independent samples t-test).